Drugs plus ligation to prevent rebleeding in cirrhosis: an updated systematic review. (24th January 2014) - Puente, Angela; Hernández‐Gea, Virginia; Graupera, Isabel; Roque, Marta; Colomo, Alan; Poca, Maria; Aracil, Carles; Gich, Ignasi; Guarner, Carlos; Villanueva, Càndid
Abstract Background & Aims Combined therapy with endoscopic variceal ligation (EVL) and β‐blockers ± isosorbide mononitrate (ISMN) is currently recommended to prevent variceal rebleeding. However, the role of this combined therapy has been challenged by some studies. We performed a systematic review to assess the value of combined therapy with EVL and β‐blockers ± ISMN as compared with each treatment alone to prevent rebleeding. Methods Databases, references and meeting abstracts were searched to retrieve randomized trials comparing combined therapy with EVL and β‐blockers ± ISMN vs either treatment alone, to prevent variceal rebleeding in cirrhosis. Random‐effects model was used for meta‐analysis. Results We identified five studies comparing EVL alone or combined with drugs, including a total of 476 patients. Combination therapy reduced overall rebleeding [risk ratios (RR) = 0.44, 95% confidence interval (CI) = 0.28–0.69], and showed a trend towards lower mortality (RR = 0.58, 95% CI = 0.33–1.03), without increasing complications. We identified four trials comparing drugs alone or associated with EVL, including 409 patients. All used β‐blockers plus ISMN. Variceal rebleeding decreased with combined therapy (P < 0.01) but rebleeding from oesophageal ulcers increased (P = 0.01). Overall, there was a trend towards lower rebleeding (RR = 0.76, 95% CI = 0.58–1.00) without effect on mortality (RR = 1.24, 95% CI = 0.90–1.70). Conclusions The addition of drug therapy to EVL improves the efficacy of EVL alone. However, the addition of EVL to β‐blockers and ISMN achieves a non‐significant decrease of rebleeding with no effect on mortality. Although combination therapy with EVL plus β‐blockers ± ISMN is adequate to prevent rebleeding, β‐blockers + ISMN alone may be a valid alternative.